Studies On The Performance Of Mild Steel-Alumina Joining Fabricated Via Friction Welding [TA470. Z21 2008 f rb]. - Noh, Mohamad Zaky (2008)
Joining of metal-ceramic can be done by different techniques such as brazing, diffusion bonding and friction welding. The joint strength of metal and ceramic has been studied extensively due to the differences in their mechanical and chemical properties.